Decentralized Application for Charity Organization Crowdfunding using Smart Contract and Blockchain - Lee, Winson; Rahim, Nordiana (Applied Information Technology And Computer Science, 2021)
There are limitations as to the current centralization of crowdfunding web applications that are found online. The first problem found in this project is the issue of integrity involving important assets such as transactional records in crowdfunding. The second issue is the issue of traceability whereby modifications in the assets should be traceable with evidence. Lastly, the issue of third-party dependency and no point-to-point transfer. This project aims to develop, design, and evaluate the crowdfunding web application system based on blockchain using smart contract. The scope of the project is open to all registered users who want to use the website for crowdfunding purpose. The expected result of this project is allowing individuals to register their accounts and start the process of crowdfunding by transferring their cryptocurrency online.